A study on Bangladesh Power Development Board on the basis of key performance indicator regarding compliance of PPR 2008 in the procurement activities in terms of procurement processing time. - Hossain, Md. Moktar (BRAC University, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.